Thirty Years of World Bank Shelter Lending : What Have We Learned? - Buckley, Robert M.; Kalarickal, Jerry (Washington, DC: World Bank, 2012)
By reviewing the Bank's experience with shelter lending, this paper seeks to address the question of whether the Bank has helped developing countries deal with the inevitable problems that arise with urbanization, particularly problems with the provision of shelter. It reviews the Bank's performance, with a focus on identifying lessons learned so that current demands can be more effectively addressed. In contrast to earlier studies, however, this review focuses more on how the changing policy environment has affected the structure of Bank assistance, rather than on how Bank assistance has affected the policy environment. This perspective is taken for two reasons. First, in recent years, benevolent changes in the policy environment are helping to ensure that better shelter conditions are provided to the poor in rapidly growing cities. However, despite the generally improved environment, some serious and often long-standing obstacles are impeding and, in some places, preventing progress. The emphasis on the policy environment allows the Bank to give greater weight to these constraints. Second, Bank shelter assistance is no longer an experimental program, as it was when the first review took place. Shelter assistance is now a mature sector, with 278 loans (including International Finance Corporation [IFC] loans). As a result, this review devotes considerably more attention to the outcomes of the Bank's shelter projects than did the earlier studies. Conclusions about shelter lending are by no means completely positive, however. In particular, while the nature of the lending has evolved to embrace the private sector more fully, it has also moved away from the poverty orientation that was for many years the core focus. If the Bank is to make a meaningful contribution to the Millennium Development Goal of affecting the lives of 100 million slum dwellers, this trend will have to change.